2019
DOI: 10.1007/s12192-018-0953-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic astrocyte-derived neurotropic factor is an important factor in chondrocyte ER homeostasis

Abstract: Mesencephalic astrocyte-derived neurotrophic factor (MANF) is an endoplasmic reticulum (ER) resident protein that can be secreted due to an imperfect KDEL motif. MANF plays a cytoprotective role in several soft tissues and is upregulated in conditions resulting from intracellular retention of mutant protein, including two skeletal diseases, metaphyseal chondrodysplasia, Schmid type (MCDS) and multiple epiphyseal dysplasia (MED). The role of MANF in skeletal tissue homeostasis is currently unknown. Interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 55 publications
(96 reference statements)
2
22
0
Order By: Relevance
“…In contrast to global Manf -/mice in the ICR strain that die prematurely (Lindahl et al, 2014) and Manf -/mice in the C57BL/6 strain that are perinatal lethal (Neves et al, 2016;Bell et al, 2019), Manf fl/fl ::Nestin Cre/1 mice were viable and visibly similar to littermates when followed until the age of 18 months. The body weights of Manf fl/fl ::Nestin Cre/1 mice were reduced at four and 16 months of age compared with the Manf fl/fl controls but when comparing Manf fl/fl :: Nestin Cre/1 mice with Nestin Cre/1 mice, there was no difference in body weight ( Fig.…”
Section: Conditional Deletion Of Manf In the Nervous Systemmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to global Manf -/mice in the ICR strain that die prematurely (Lindahl et al, 2014) and Manf -/mice in the C57BL/6 strain that are perinatal lethal (Neves et al, 2016;Bell et al, 2019), Manf fl/fl ::Nestin Cre/1 mice were viable and visibly similar to littermates when followed until the age of 18 months. The body weights of Manf fl/fl ::Nestin Cre/1 mice were reduced at four and 16 months of age compared with the Manf fl/fl controls but when comparing Manf fl/fl :: Nestin Cre/1 mice with Nestin Cre/1 mice, there was no difference in body weight ( Fig.…”
Section: Conditional Deletion Of Manf In the Nervous Systemmentioning
confidence: 81%
“…Previously it has been shown that loss of MANF in pancreatic b cells leads to chronic UPR activation in vivo (Lindahl et al, 2014). Recently, it was also demonstrated that ablation of MANF in cartilage results in upregulation of ER chaperones in vivo (Bell et al, 2019). Therefore, we examined the expression of UPR-related genes in the brains of both conventional Manf -/and conditional Manf fl/fl :: Nestin Cre/1 KO mice.…”
Section: Manf Deficiency Causes Robust Activation Of Ire1a Signaling mentioning
confidence: 98%
“…Of note, both l-and s-group mutants showed other phenotypic changes typical to the Manf KO mice, namely hyperglycemia and reduced growth (Fig. 2f, g) 4,5 .…”
Section: Manf Ko Mice Show Progressive Outer Hair Cell Loss and Elevamentioning
confidence: 86%
“…Analysis of the Manf loss-of-function mutant mice has shown that the insulin-producing beta cells of the pancreas are particularly sensitive to Manf deficiency; they die from the juvenile stages onward, leading to diabetes 4 . The mouse strain has an impact on the Manf knock out (KO) phenotype: KO mice under the C57BL/6J (BL6) background die perinatally due to respiratory problems, whereas most KOs under the CD-1 background survive to adulthood 4,5 . Thus, available data give evidence that MANF promotes cell survival in a cell context-dependent and genetic backgrounddependent fashion.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has identified the importance of MANF for skeletal growth (59). Cartilage-specific ablation of Manf in mice led to skeletal dysplasias caused by reduced chondrocyte proliferation and increased ER stress.…”
Section: Discussionmentioning
confidence: 99%